Analisis Kontrastif Verba Khusus Keigo dengan Verba Khusus Undak Unduk Basa - Gustini, Maria (Jurnal SORA - Pernik Studi Bahasa Asing, 2023)
This study discusses the contrastive analysis of Japanese honorific (keigo) with Sundanese honorific (undak unduk basa). This research was conducted to obtain similarities and differences between the two types of honorific. The data used in this study are sentences and dialogues that use a variety of honorifics in Japanese and Sundanese corpus, movies, and books. This study used a descriptive method and data collection was carried out through recording techniques. Based on data analysis, similarities and differences can be found in both types of honorific. From the four pairs of special verbs contrasted, it can be concluded that there are similarities including the verbs meshiagaru/pour, itadaku/neda, irassharu/angkat and mairu/mios can be translated as equalized, but the four pairs of special verbs have different contexts in their use due to the steps that can be used in the uchi environment (closest to the speaker) while keigo cannot be used in the immediate environment.